Molecular mechanism of acquired drug resistance in the EGFR‐TKI resistant cell line HCC827‐TR - Tao Yu; Qian Xia; Ting Gong; Jing Wang; DianSheng Zhong (Thoracic Cancer)
Abstract Background The first‐line standard treatment of non‐small cell lung cancer (NSCLC) with EGFR mutation is EGFR‐tyrosine kinase inhibitors (TKIs). However, most patients will develop acquired resistance after 9–13 months. This study investigated novel molecular mechanisms of acquired resistance to EGFR‐TKIs to identify a potential new treatment for EGFR‐TKI resistant NSCLC patients. Methods We established an EGFR‐TKI resistant cell line (HCC827‐TR) by culturing the HCC827‐P cell line through continuous erlotinib culture. We used Sanger sequencing, RT‐PCR, and western blot to rule out known resistance mechanisms in HCC827‐TR cells, including EGFR‐T790M and MET, PTEN, or EGFR expression changes. Next‐generation sequencing was performed and identified differentially expressed genes between two cell lines and examined the genes with GO and KEGG pathway database analyses. We also examined the molecular alterations in COSMIC and GDSC databases and performed hazard predictions using SIFT, PolyPhen‐2, Mutation Taster, and CADD. Results Our results identified FGF2 as a differentially expressed gene with a G101T point mutation in HCC827‐TR cells that showed high mutation frequency and hazard score. HCC827‐TR cells showed elevated FGF2 compared to parental cells. It is noteworthy that treatment with the FGFR inhibitor AZD4547 could restore the sensitivity of HCC872‐TR cells to erlotinib. Conclusions An erlotinib‐resistant cell line HCC827‐TR was successfully constructed and we identified the EGFR‐TKI resistance mechanism involving the FGF2 gene mutation. Targeted inhibition of the FGF2/FGFR signaling pathway may effectively restore the sensitivity of the resistant cells to erlotinib. These results suggest a novel treatment strategy for EGFR‐TKI resistant NSCLC patients. Key points Significant findings of the study: Identifies a novel molecular mechanism for EGFR‐TKI acquired resistance. What this study adds: A potential novel strategy for the treatment of EGFR‐TKI resistant NSCLC patients.